Innovation for Empowering People with Schizophrenia in Empowered Homes Denpasar City - Puspasari, Herti Windya; Sitorus, Nikson; Agustiya, Rozana Ika; Pranata, Setia; Isfandari, Siti; Rachmawati, Tety (Indigenous, 2023)
Abstract. The problem in mental health services is recurrence in patients. One of the efforts to prevent recurrence is through People With Schizophrenoia (PWS) empowerment at the Rumah Berdaya in Denpasar City. This study is aimed to describe the innovation of PWS empowerment in Rumah Berdaya. It is a qualitative study using a case study design to get more information about the role and innovation empowerment of PWS in Rumah Berdaya. Qualitative data collected employed in-depth interview methods with interview guideline instruments. Informants were selected based on purposive sampling. The results showed that there were several innovations in empowering for PWS in Rumah Berdaya. There are recruitment of controlled PWS as honorary workers in the social service Denpasar City to work in Rumah Berdaya, Purchase of incense produced by PWS Rumah Berdaya for use in all the agencies government denpasar city, making coconut oil, paintings, screen printing t-shirts and tote bags by PWS and then sold offline at Rumah Berdaya and online by social media, assistance for PWS family with family support, dissemination and education to the community with the aim for reducing negative stigma of PWS. Therefore, Rumah Berdaya has contributed for PWS rehabilitation process in Denpasar city. Collaboration between the government by social services and health offices, volunteers, and community to support the empowerment of PWS in Rumah Berdaya has been effective. The strong commitment is needed to support the sustainability of the empowerment program at Rumah Berdaya.Keywords: Empowerment; innovation; schizophrenia.